The association between sedentary behavioral characteristics and poor vision among Chinese children and adolescents - Li, Lin; Liao, Jinjin; Fu, Hui; Zong, Boyi (Frontiers in Public Health, 2022)
Introduction To understand the features of sedentary behavior of Chinese children and adolescents and its relationship with poor visual acuity, a self-administered “Questionnaire on Sedentary Behavior of Children and Adolescents” was used to survey 4,203 students in grades 4–12 in six administrative regions of China. Results (1) The average time spent in sedentary behaviors (SB) of Chinese children and adolescents was about 8.1 h per day, of which the academic sedentary time was the longest, accounting for 79.2% of total sedentary time. The total time spent on SB and the time spent on studying SB were more in the upper grades and less in screen SB and cultural leisure SB, respectively. There were significant sex differences in total SB time (p < 0.05) and weekend sedentary behaviors time (SB-WD) (p < 0.01) among Chinese children and adolescents, with girls being more likely to be higher than boys. There were also significant differences in sedentary time across different regions (p < 0.05), and the longest total sedentary time in East China. (2) Reduction parents' sedentary time and limitation of sedentary behaviors and the use of electronics among children and adolescents can effectively reduce sedentary time among Chinese children and adolescents. (3) Sedentary time was significantly higher in children and adolescents with poor vision than in those with normal vision (p < 0.01), and study SB and screen SB were important independent factors affecting vision. (4) Timing of breaks in SB can play a positive role in promoting vision health. Conclusion There were significant grade, sex, and regional differences in the SB of Chinese children and adolescents, and sedentary time was strongly related to the prevalence of poor vision detection rate.